1997
DOI: 10.1038/sj.sc.3100437
|View full text |Cite
|
Sign up to set email alerts
|

Psychological investigation of spinal cord injury patients

Abstract: Spinal cord injuries (SCI) often have psychological consequences, primarily anxiety and depression, which may interfere with rehabilitation possibilities, with adjustment to the impairment and therefore with the possibility of returning to previous familiar social life and work. To assess the degree of anxiety and depression in SCI patients, and to study the factors contributing to their genesis, 100 SCI in-and out-patients were administered questionnaires for self-rating anxiety and depression. A group of new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
43
3
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 14 publications
6
43
3
2
Order By: Relevance
“…Notably, accommodations were made for the STAI, with elevated cutoff scores for self-reported 'clinical caseness' utilised in an attempt to improve test specificity and, in turn, achieve reliable estimates of anxiety prevalence. 12,27,37 The STAI is considered a comprehensive 40-item scale that has demonstrated applicability in populations with chronic conditions. 12 Further research is, however, still needed to confirm the utility of proposed cutoff scores.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Notably, accommodations were made for the STAI, with elevated cutoff scores for self-reported 'clinical caseness' utilised in an attempt to improve test specificity and, in turn, achieve reliable estimates of anxiety prevalence. 12,27,37 The STAI is considered a comprehensive 40-item scale that has demonstrated applicability in populations with chronic conditions. 12 Further research is, however, still needed to confirm the utility of proposed cutoff scores.…”
Section: Discussionmentioning
confidence: 99%
“…The full-texts of these studies were subsequently examined by both authors. 1,8,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] The reference lists of these studies and published SCI review papers 2,10,11,41 were additionally examined. Although this process did not lead to the discovery of any new studies, it helped ensure that all relevant papers were identified.…”
Section: Eligibility Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of anxiety and depression in SCI exceeds that of the general population, with psychological morbidity or psychological distress estimates ranging between 20 and 30%, suggesting the need for appropriate screening tools in these patients. [4][5][6][7] Most measures used to assess depression and anxiety in patients with SCI were standardized on people without physical disabilities or chronic medical conditions. 8 Importantly, incidence rates of depression in SCI are higher when based on self-report measures than when based on structured interviews.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 This burden, if excessive, may lead to emotional break-down among people with SCI. Despite the last few decades having witnessed an increase in literature regarding psychological reaction to people with SCI 3,4 and their carers 5 ± 7 there is a paucity of studies on individual conceptions of the experience of SCI. However, the few studies that address these individual conceptions of the experience of SCI are based on Western European perspective.…”
Section: Introductionmentioning
confidence: 99%